Neurofibromatosis type 1 families with first-degree relatives harbouring distinct NF1 pathogenic variants. Genetic counselling and familial diagnosis: what should be offered?. Issue 10 (4th February 2022) - Garcia, Belen; Catasus, Nuria; Ros, Andrea; Rosas, Inma; Negro, Alejandro; Guerrero-Murillo, Mercedes; Valero, Ana Maria; Duat-Rodriguez, Anna; Becerra, Juan Luis; Bonache, Sandra; Lázaro Garcia, Conxi; Comas, Carmina; et al.
Abstract : Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder caused by pathogenic variants in NF1 . Recently, NF1 testing has been included as a clinical criterion for NF1 diagnosis. Additionally, preconception genetic counselling in patients with NF1 focuses on a 50% risk of transmitting the familial variant as the risk of having a sporadic NF1 is considered the same as the general population. Methods: 829 individuals, 583 NF1 sporadic cases and 246 patients with NF1 with documented family history, underwent genetic testing for NF1. Genotyping and segregation analysis of NF1 familial variants was determined by microsatellite analysis and NF1 sequencing. Results: The mutational analysis of NF1 in 154 families with two or more affected cases studied showed the co-occurrence of two different NF1 germline pathogenic variants in four families. The estimated mutation rate in those families was 3.89×10 –3, 20 times higher than the NF1 mutation rate (~2×10 −4 ) (p=0.0008). Furthermore, the co-occurrence of two different NF1 germline pathogenic variants in these families was 1:39, 60 times the frequency of sporadic NF1 (1:2500) (p=0.003). In all cases, the de novo NF1 pathogenic variant was present in a descendant of an affected male. In two cases, variants were detected in the inherited paternal wild-type allele. Conclusions: Our results, together with previous cases reported, suggest that the offspring of male patients with NF1 could have an increased risk of experiencing de novo NF1 pathogenic variants. This observation, if confirmed in additional cohorts, could have relevant implications for NF1 genetic counselling, family planning and NF1 genetic testing.